Licensing Sentence-internal Readings in English An Experimental Study - Brasoveanu, Adrian; Dotlaˇcil, Jakub (Proceedings of the Amsterdam Colloquium, 2011)
Adjectives of comparison (AOCs) like same, different and similar can compare two elements sentence-internally, i.e., without referring to any previously introduced element. This reading can only be licensed if a semantically plural NP is present. In contrast to almost all previous literature, we argue in this paper that it is incorrect to describe a particular NP as either licensing or not licensing the sentence-internal reading of a specific AOC: licensing is more fine-grained. We use experimental methods to establish which NPs license which AOCs and to what extent. We show how the results can be interpreted against the background of a formal semantics analysis of AOCs and we argue that using Bayesian methods to analyze this kind of data has several advantages over the more traditional, frequentist approach.